Triggering and preventing cyclization of o-amino-guanidinobenzenes to 2-amino-benzimidazoles - Henel, Carmen L. M.; Michel, Edwin; Zeitler, Devin; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2026)
Aromatic compounds in which a primary or secondary amino group is positioned next (in ortho position) to a guanidino group have been reported as intermediates in a variety of reactions, but are generally prone to cyclization to give 2-amino-imidazoles. Here, we present a comprehensive analysis, based on experiments and quantum-chemical calculations, of the stability and reactivity of these compounds. It is shown that cyclization reactions are triggered by Brønsted and Lewis acids. The analysis discloses strategies allowing to prevent cyclization by careful choice of the guanidino group and/or substituent at the amino group. The results of this analysis allowed the synthesis of first unsymmetrical diguanidinobenzene molecules and coordination compounds with o-amino-guanidinobenzene ligands, paving the way for the development of aromatic compounds with adjacent amino and guanidino groups as a versatile class of redox-active organic molecules.